How Knowledge Contexts Influence Entrepreneurial Strategy, Evidence from IPO Firms - Humphrey, Jarrod; Shin, Dong Hyun (Journal of Knowledge Management Practice, 2025)
Founders inherit valuable expertise from their previous employers, which they subsequently apply in their new ventures. This study examines the differences in strategic leadership and capital allocation between academic and industry spinouts, emphasizing the impact of knowledge context on entrepreneurial strategy. Utilizing hand-collected data on all IPO firms in life sciences and computer programming, we find that academic spinouts are less likely to retain a founder as CEO compared to industry spinouts, and academic spinouts allocate more resources to R&D than industry counterparts. Furthermore, we explore how founder-CEO moderates the relationship between academic spinouts and their resource allocation to R&D.